Ultra-thin platinum interfacial layer assisted-photovoltaic response of transparent Pb(Zr, Ti)O3 thin film capacitors. (January 2015) - Anoop, G.; Seo, Juhee; Han, Chang Jo; Lee, Hyeon Jun; Kim, Gil Woong; Lee, Sung Su; Park, Eun Young; Jo, Ji Young
Highlights: Transparent Pb(Zr, Ti)O3 (PZT) capacitors were fabricated using cost-effective solution process. Photovoltaic response was investigated by introducing ultra-thin Pt layer between bottom electrode and PZT. Introduction of Pt layer reduces the leakage current and enhances ferroelectric and PV response. The transmittance of the capacitors were 45–50% in visible region. Abstract: For transparent solar cells, Sn:In2 O3 /Pb(Zr, Ti)TiO3 /Pt(⩽5 nm)/Sn:In2 O3 capacitor structures were fabricated using a cost-effective solution process. The insertion of ultra-thin Pt layer between the bottom Sn:In2 O3 electrode and Pb(Zr, Ti)TiO3 plays a critical role in the photovoltaic characteristics of the capacitors. The Pb(Zr, Ti)O3 capacitors with a 5 nm thick Pt layer showed excellent polarization–voltage curves with reduced leakage current due to both partial (1 1 1) orientation of Pb(Zr, Ti)O3 and alloy formation between Pt and the Sn:In2 O3 bottom electrode, as confirmed using X-ray photoelectron spectra analysis. The capacitors with a 5 nm thick Pt layer exhibit transmittance of 45–50% in the visible light region. The current density–voltage characteristics under light illumination (AM1.5G) exhibit an open circuit voltage value of −0.62 V and short circuit current density of 0.6 μA/cm 2 after negative poling, with a maximum power conversion efficiency of 1.7 × 10 −4 %. The open circuit voltage of the capacitors with a 5 nm thick Pt layer is larger with negative poling due to the higher net internal bias arising from the Schottky barrier.